SRTATEGI POLITIK BANJAR ADAT CANGGU MELAWAN MASUKNYA TRANSPORTASI ONLINE DI DAERAH CANGGU - Bawa Partika, Kadek Alit Dwi; Azhar, Muh. Ali; Noak, Piers Andreas (Jurnal Nawala Politika, 2021)
This study described the political strategy of the Banjar Adat and conventional taxi associations in Canggu against online transportation. This study was used explanative research with qualitative methods. The theories used in this study were political strategy theory and institutional theory as well as the concept of political planning and the concept of lobbying and negotiation. The results showed that the strategic process carried out by the Banjar and conventional taxi associations in Canggu was divided into three parts. First, the publication of a customary regulation on the prohibition of online transportation. Second, to lobby members of the Regional House of Representatives from Canggu. Third, held a demonstration demanding the Governor of Bali to issue regulations as law protection. Based on the various strategies that were carried out, the Governor of Bali finally issued Governor Regulation No.2 of 2020 concerning online transportation arrangements. Keywords: Banjar Adat, Institutional Strategy, Online Transportation.